1998
DOI: 10.1590/s0100-40421998000600009
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective sodium borohydride reductions of cyclopentanones: influence of ceric chloride on the stereochemistry of reaction

Abstract: Recebido em 22/8/97; aceito em 23/1/98In this paper we describe the reduction by NaBH 4 of some cyclopentanones containing an oxygenated function at the side chain position β β β β β to the carbonyl group, both in the presence and in the absence of CeCl 3 . Some suggestions for the rationalization of the results are discussed, considering the stereochemical course of the reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
6

Year Published

2003
2003
2010
2010

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 2 publications
0
11
0
6
Order By: Relevance
“…1) were first prepared from isophorone in our laboratory for synthetic studies purposes, 5,6 as shown in Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1) were first prepared from isophorone in our laboratory for synthetic studies purposes, 5,6 as shown in Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
“…Cyclopentane derivatives are important intermediates in organic synthesis; 5,6 the determination of the structure and relative stereochemistry of these compounds is frequently a difficult task. In previous studies, we have shown that the long-range homonuclear spin-spin coupling constant cannot be reduced to the simple rule of planar W conformation.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 For the measurements reported in this paper they were prepared as previously described, and then purified (mainly by column chromatography) until clean spectra were obtained. For the assignment of the 1 H and 13 C NMR spectra of 1-8, a combination of two-dimensional J-resolved and HMQC experiments were carried out.…”
Section: Resultsmentioning
confidence: 99%
“…[1,2] However, the determination of the structure and the relative stereochemistry of these compounds is frequently a difficult task, due to the various conformers that these compounds can exhibit.…”
Section: Stereochemistry Of Cyclopentane Derivatives From 23 J Ch Dementioning
confidence: 99%